2014
DOI: 10.1016/j.acthis.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Tualang honey supplement improves memory performance and hippocampal morphology in stressed ovariectomized rats

Abstract: Recently, our research team has reported that Tualang honey was able to improve immediate memory in postmenopausal women comparable with that of estrogen progestin therapy. Therefore the aim of the present study was to examine the effects of Tualang honey supplement on hippocampal morphology and memory performance in ovariectomized (OVX) rats exposed to social instability stress. Female Sprague-Dawley rats were divided into six groups: (i) sham-operated controls, (ii) stressed sham-operated controls, (iii) OVX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 113 publications
4
42
0
Order By: Relevance
“…Therefore, it is suggested that the memory enhancing effects of Tualang honey could be due to the enhancement of neuronal proliferation in mPFC and hippocampus, a result paralleled to the previous study done in stressed ovariectomized rats [32]. Another study demonstrated that honey effectively inhibited apoptosis or neuronal cell death in the hippocampus of streptozotocin-induced diabetic rats [70].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Therefore, it is suggested that the memory enhancing effects of Tualang honey could be due to the enhancement of neuronal proliferation in mPFC and hippocampus, a result paralleled to the previous study done in stressed ovariectomized rats [32]. Another study demonstrated that honey effectively inhibited apoptosis or neuronal cell death in the hippocampus of streptozotocin-induced diabetic rats [70].…”
Section: Discussionsupporting
confidence: 69%
“…Correspondingly, another study reported that consumptions of honey may improve spatial memory in middle-aged rats compared to those sucrose-fed or sugar-free diet [31]. In closely related studies, it was demonstrated that Tualang honey was able to improve memory performance in stressed ovariectomized rats [32] and postmenopausal women [33]. Therefore, it is hypothesized that Tualang honey could revert oxidative stress by removing the ROS that were produced during noise stress and thus prevent oxidative damage in memoryrelated brain areas, particularly in aged rats.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The tissues were then dehydrated in a gradient of alcohol, cleared with xylene (C0900‐2190239, HmbG Inc., Germany), and mounted in DPX mounting medium (360294H, BDH Chemicals, UK). Tissue sections were covered with coverslips (G0543, HmbG Inc. Germany) and observed and analyzed with a light microscope with an image analyzer (20 × objective lens power) (Olympus, BX‐14‐32PO2, Olympus Corporation, Japan) by three blinded investigators (Al‐Rahbi et al., 2014; Moorthi, Premkumar, Priyanka, Jayachandran, & Anusuyadevi, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Tualang honey showed its ability to improve learning and memory in clinical 23 as well as experimental studies 24 . these activities of tualang honey can be attributed to its ability to stimulate the cholinergic system and improve the morphology of the brain.…”
Section: -Improvement Of Learning and Memorymentioning
confidence: 99%